International health care reform : a legal, economic, and political analysis - Flood, Colleen M. (Routledge studies in the modern world economy, 2000)
This book analyses the wave of competition-oriented reform by comparing ""internal market reform"" (proposed in publicly-funded health care systems) with ""managed competition reform"" (proposed in systems with a mixture of public/private financing) and the role of ""managed care"" in each of these reform theories. International Health Care Reform clearly explains the arguments in economics and justice for intervention by governments in health care markets; the structure and dynamics of health care systems; and the features of competition-oriented reform models. The book will app